2022
DOI: 10.1113/jp282279
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT7 receptors expressed in the mouse parafacial region are not required for respiratory chemosensitivity

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In this issue of The Journal of Physiology , Shi et al . (2022) revisit a previous hypothesis that raphe‐derived serotonin (5‐HT) drives the chemosensitivity of RTN neurons through the activation of 5‐HT 7 receptors (5‐HT 7 R). This possibility was proposed by Wu et al .…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…In this issue of The Journal of Physiology , Shi et al . (2022) revisit a previous hypothesis that raphe‐derived serotonin (5‐HT) drives the chemosensitivity of RTN neurons through the activation of 5‐HT 7 receptors (5‐HT 7 R). This possibility was proposed by Wu et al .…”
mentioning
confidence: 93%
“…Finally, it was demonstrated that the bilateral 5-HT 7 R antagonism in the parafacial region did not modify the hypercapnic ventilatory response in freely behaving mice, although microinjections of a 5-HT 7 R agonist in the same area stimulated breathing. The data provided by Shi et al (2022) showing that the RTN chemosensitivity and the hypercapnic ventilatory response do not require the activation of 5-HT 7 R in the parafacial region are compelling and in contrast to the observations reported by Wu et al (2019). Both studies show scientific quality and relevance; however, the work by Shi et al (2022) highlights the importance of revisiting and confirming critical questions further using refined and more accurate methodologies.…”
mentioning
confidence: 95%
See 3 more Smart Citations